Oxigenoterapia y su influencia en la evolución de la enfermedad pulmonar obstructiva crónica en adultos que asisten al área de observación Hospital Martín Icaza Babahoyo Los Ríos primer semestre 2018 - Loor Chichande, Yedarly Adriana (2018)
This research project is based on the appearance of COPD, which is a respiratory difficulty that affects airflow causing a severe obstruction in the pulmonary bronchi. Where smoking is the main cause of developing COPD, where it is estimated between 23% and 31% of active smokers. The objective of this research is to apply strategies with adequate procedures in order to improve Chronic Obstructive Pulmonary Disease in adults who attend the observation area of the Martin Icaza Babahoyo Hospital in the first semester 2018. With the purpose of improving the quality of life of patients with COPD. As a methodology used in this descriptive and exploratory study research and as a deductive-inductive research method, where a sample of 95 people was used, where 45 people suffered from Chronic Obstructive Pulmonary Disease. Obtaining as a result of the survey applied in Martin Icaza Hospital of 58% are active smokers and have developed COPD due to tobacco, in addition that 59% have knowledge of the evolution of this pathology with the treatment of oxygen therapy. It is recommended to deepen the information collected from patients for more effective treatment of oxygen therapy of chronic obstructive pulmonary disease, in addition those patients perform pulmonary rehabilitation to achieve a good quality of life. And it is proposed as a proposal to implement training methods on the risks, prevention and complications of COPD; as the development of demonstration workshops of oxygen therapy in the treatment of patients with Chronic Obstructive Pulmonary Disease about the beneficial effects of such therapy to improve the quality of life of adults attending the Martin Icaza Hospital.